Decreased mRNA expression of netrin-G1 and netrin-G2 in the temporal lobe in schizophrenia and bipolar disorder. - Eastwood, S; Harrison, P (2008)
The membrane-bound axon guidance molecules netrin-G1 (NTNG1) and netrin-G2 (NTNG2) play a role in synaptic formation and maintenance. Non-coding single nucleotide polymorphisms (SNPs) in both genes have been reported to be associated with schizophrenia. The main aim of this study was to determine if NTNG1 and NTNG2 mRNA expression is altered in schizophrenia or bipolar disorder, and/or influenced by disease-associated SNPs. NTNG1 and NTNG2 mRNAs were examined in the medial and inferior temporal lobe using in situ hybridization and RT-PCR in the Stanley Medical Research Institute array collection, and in rat hippocampus during development and after antipsychotic administration. NTNG1 mRNA isoforms were also examined during human brain development. For NTNG1, the G1c isoform was reduced in bipolar disorder and with a similar trend in schizophrenia; expression of four other NTNG1 isoforms was unchanged. In both schizophrenia and bipolar disorder, NTNG2 mRNA was reduced in CA3, with reductions also found in CA4 and perirhinal cortex in bipolar disorder. The SNPs did not affect NTNG1 or NTNG2 mRNA expression. Both NTNG1 and NTNG2 mRNAs were developmentally regulated, and were unaltered by haloperidol, but NTNG2 mRNA was modestly increased by clozapine. These data implicate NTNG1 and NTNG2 in the pathophysiology of schizophrenia and bipolar disorder, but do not support the hypothesis that altered mRNA expression is the mechanism by which genetic variation of NTNG1 or NTNG2 may confer disease susceptibility.